Waste to wealth: Incinerated municipal solid waste ash / Salmaliza Salleh - Salleh, Salmaliza (Universiti Teknologi MARA Cawangan Pahang, 2008)
In developing countries such as Malaysia, waste management is becoming an acute problem as urbanisation and economic development increased rapidly. Due to deficient of landfill spaces, incineration is gaining increasing consideration from the government as an alternative method of solid waste management. Although 95% reduction in solid waste volume can be achieved by incineration, it produces large amount of ashes. Using the concept of powder metallurgy, the ash is treated as powder and its commercial potential is discussed.